PELATIHAN KREATIF MENGAJAR: PEMBERDAYAAN GURU MELALUI MEDIA E-KOMIK DAN MUSIK UNTUK MENINGKATKAN LITERASI DAN NUMERASI SISWA - Tita Ratna Wulan Dari Dari; Sary Silvhiany; Septy Sari Yukans; Fathimah Nurul Izzah; Afzal Rasendriya (Jurnal Abdi Insani, 2026)
The Education Report serves as a key indicator of the quality and performance of an educational institution. SMP Sandika, a junior high school located in Talang Kelapa, Banyuasin, is currently facing challenges in meeting the targets set by the Computer-Based National Assessment (ANBK), resulting in a predominantly low performance as indicated by the red status in the report. In response, this community service program was designed to enhance teachers' pedagogical capacity through creative teaching training, utilizing e-comics and music as instructional tools to support the strengthening of students’ literacy and numeracy skills. Based on a needs assessment conducted at the partner school, it was found that most teachers still applied conventional teaching methods and faced difficulties in developing contextual, engaging, and adaptive teaching media. The training was carried out using a participatory approach involving interactive lectures, group discussions, and hands-on practice. A total of 22 teachers from various academic backgrounds participated in the training sessions held at SMP Sandika. Evaluation results revealed a significant improvement in teachers' understanding. Prior to the training, only 53.40% of participants demonstrated comprehension of literacy concepts, and 67.04% understood numeracy. Post-training, these figures increased to 85.22% and 89.77% respectively. Open-ended responses also showed a shift in perspective regarding instructional strategies; initially, no participants mentioned e-comics or music as possible tools, but post-training, many included them as viable strategies. These findings demonstrate that the training effectively improved teacher competence, particularly in designing creative, digitally-based learning experiences. This initiative is expected to contribute significantly to the improvement of education quality, especially in enhancing SMP Sandika’s performance report and the broader educational outcomes in Banyuasin Regency.